Pengaruh Live Streaming Dan Persepsi Harga Terhadap Keputusan Pembelian Konsumen UMKM Di Tangerang - Wahyudi, Widi; Marsin, Marsin; Aris Wahyu Kuncoro (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The increasing intensity of competition among micro, small, and medium enterprises (MSMEs) in Tangerang City is encouraging businesses to utilize digital marketing strategies that create direct interactions with consumers. One emerging approach is live streaming, which allows for the delivery of product information in real time while fostering two-way communication between sellers and consumers. In addition to promotional strategies, price perception also plays a role in shaping consumers' evaluations of the product's value. This study aims to examine the influence of live streaming and price perception on MSME consumer purchasing decisions in Tangerang City. A quantitative approach was used, using a survey method with 50 MSME consumer respondents. Data collection was conducted using a five-point Likert-scale questionnaire that underwent validity and reliability testing. Data analysis included classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that live streaming and price perception have a positive and significant effect on purchasing decisions, both partially and simultaneously. This finding confirms that the success of MSME digital marketing is determined not only by the intensity of interactive promotions, but also by the business owner's ability to build price perceptions that align with product value.